Nineteenth-century communications
1 online resource (560 pages)
Keywords: This volume foregrounds the close, and mutually informing, relationships between mediated communication and technological innovation during the nineteenth century. It draws attention to the fact that communication was a driver of innovation, but also considers how communication practices adapted to new media and technologies. The following themes and subjects are covered: The development of the telegraph, from the semaphore in the late eighteenth century to the wireless in the late nineteenth. Rhe shift from privately owned to nationalised telegraph infrastructure and services. Mail trains, travelling post offices, and accelerated public communication. The development of and cultural responses to steam-packet technologies and infrastructures, and accelerated international communication. The development of and cultural responses to submarine and transoceanic telegraphy. The beginnings of telephony.